Incumbency, diversity, and latitudinal gradients. Issue 2 (8th April 2008) - Valentine, James W.; Jablonski, David; Krug, Andrew Z.; Roy, Kaustuv
Abstract : Physical environmental factors have been seen as paramount in determining many large-scale biodistributional patterns in time and space. Although this is probably correct for many situations, this view has become so pervasive that it has led to the neglect of the role of biotic interactions in setting large-scale diversity patterns. (In this paper diversity denotes taxonomic richness.) New approaches to this perennial debate on the roles of physical and biotic forces in paleoecology and macroevolution are needed, and here we explore an argument for the role of incumbency or priority effects in the dynamics behind the most dramatic spatial pattern in biodiversity, the latitudinal diversity gradient.